ナンキョク オオガタ セツジョウシャ (SM100S) ノ カイハツ IV. ゴム リタイ ノ テイオン トクセイ - 前川, 悦治; マエカワ, エツジ; 寺山, 義英; テラヤマ, ヨシヒデ; Maekawa, Etsuji; Terayama, Yoshihide (1992)
P(論文) 耐超低温特性の観点から, 最近開発されたイソプレン・ブタジエン共重合体の雪上車用履帯ゴムとしての実用の可否を現行の天然ゴムのみの系と天然ゴム/ブタジエンゴムのブレンド系との比較において検討した。その結果, 強度的にはこれら二者より劣るが, -70℃においても十分なゴム弾性を保持しており, 実用試験をしてみる価値があることがわかった。 In order to discover a high cold-resistance material for use in the crawler belt of snow vehicles, the physical properties at very low temperatures of a recently developed material, isoprene/butadiene (70/30) random copolymer filled with carbon black, was investigated in comparison with a blended rubber NR/BR (65/35) as well as a currently used NR. It has been found that this material can keep rubber elasticity even at low temperatures blow -70℃, though it is somewhat inferior to the other two materials as to strengths such as stress-at-break and tear; and hence, it is considered as quite worthy of a practical test under equipped for a snow vehicle in the Antarctic area. departmental bulletin paper